1994
DOI: 10.1210/endo.135.5.7956912
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone enhances macrophage colony-stimulating factor production in human endometrial stromal cells in vitro.

Abstract: Increasing evidence suggests that macrophage colony-stimulating factor (M-CSF) is produced in the uterine endometrium and that it plays an important role in the reproductive process. In the present study, using an in vitro decidualization model and human endometrium, we investigated M-CSF messenger RNA (mRNA) expression in human endometrial stromal cells (ESC) by Northern blotting and in situ hybridization. The secreted M-CSF in the culture medium of ESC was measured by enzyme-linked immunosorbent assay. ESC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…Accordingly, increased local and circulating GM-CSF levels have been associated with preeclampsia, an inflammatory placenta disorder (65,66), although other reports failed to demonstrate such associations (67,68). Our results suggest that the balance between M-CSF and GM-CSF at the fetal-maternal interface needs to be strictly regulated, which might be done, at least in part, by progesterone, which has been shown to upregulate M-CSF and downregulate GM-CSF (53,69). It is also notable that IL-10, but not the Th2 cytokines IL-4 and IL-13, was able to restore the GM-CSF-mediated inhibition of the decidual Mf phenotype, supporting the concept of an M-CSF-and IL-10-driven homeostatic and tolerogenic, rather than a Th2-dominated, local environment in early pregnancy.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Accordingly, increased local and circulating GM-CSF levels have been associated with preeclampsia, an inflammatory placenta disorder (65,66), although other reports failed to demonstrate such associations (67,68). Our results suggest that the balance between M-CSF and GM-CSF at the fetal-maternal interface needs to be strictly regulated, which might be done, at least in part, by progesterone, which has been shown to upregulate M-CSF and downregulate GM-CSF (53,69). It is also notable that IL-10, but not the Th2 cytokines IL-4 and IL-13, was able to restore the GM-CSF-mediated inhibition of the decidual Mf phenotype, supporting the concept of an M-CSF-and IL-10-driven homeostatic and tolerogenic, rather than a Th2-dominated, local environment in early pregnancy.…”
Section: Discussionmentioning
confidence: 49%
“…Similarly, IL-10 is constitutively produced by a variety of cells and is also induced in inflammatory conditions to counteract proinflammatory cytokines, thereby considered as an important homeostatic mechanism to avoid inappropriate T cell activation (49). In the context of pregnancy, IL-10 is locally produced by, for example, trophoblasts, uterine NK cells, and Mf (22,50,51), and M-CSF, which increases dramatically in the mouse and human uterus during gestation (26,28), is produced by, for example, endometrial stromal cells, trophoblasts, and uterine NK cells (52,53). Thus, it is likely that the locally produced M-CSF and IL-10 promote homeostatic Mf with the ability of clearing infections without compromising fetal tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of danazol on ESC activation into G-CSF-secreting cells are opposite to the effects of M-CSF, which induces ESC activation into G-CSF-secreting cells. M-CSF is produced in the human endometrium, particularly by decidual cells (33,34). IL-8 secretion by ESCs is regulated by endometrial IL-1 and IL-1 receptor antagonist (31).…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers have reported that M-CSF and its receptor are expressed in the female reproductive tract and that M-CSF plays an important role in pregnancy in mice [1,2,[21][22][23], humans [8,[11][12][13], pigs [35] and cows [3,17,19]. Furthermore, M-CSF concentrations in maternal peripheral blood during the estrous cycle and pregnancy have been reported in humans and mice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, human endometrial, decidual and placental tissues have been found to express M-CSF mRNA and have demonstrated extractable immunoreactive M-CSF [8,12,13]. Human M-CSF, in a concentration-dependent manner, increases the secretion of human chorionic gonadotropin from primary cultured human cytotrophoblastic cells and a human placental cell line [27].…”
mentioning
confidence: 97%